PENGARUH KUALITAS LAYANAN TERHADAP KEPUTUSAN KUNJUNGAN WISATA KE DANAU TOBA SELAMA PANDEMI COVID-19 - Poltak Pardamean Simarmata; Muhammad Yunus (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
The Covid-19 pandemic had heavily affected Indonesian economy, especially for the tourism sector. The Indonesian government has taken numerous measures to respond to the Covid -19 pandemic such as large-scale social restrictions, restrictions on community activities, in which reduces community and impact on the tourism sector inevitably. The purpose of the study was to determine the influence of service quality on the decision to visit Lake Toba tourist destinations. The research activity was carried out in Parapat, Simalungun Regency. This research uses descriptive and quantitative methods. Data were collected from observations, interviews, and questionnaires. The sample used was 100 tourist respondents who visited Lake Toba Parapat during the Covid-19 pandemic. Data were analyzed by simple linear regression analysis. The test results have a positive and significant effect on service quality on the decision to visit Lake Toba tourist destinations. The influence of the service quality variable on the visit decision variable is 0.10, the remaining 0.80 is influenced by other factors not examined in this study such as psychological factors, economic factors during the Covid-19 pandemic. Efforts to increase tourist visits during the Covid-19 pandemic are carried out by paying attention to the tangible dimension and increasing other dimensions in service quality.